2015
DOI: 10.1016/j.actamat.2015.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of radiation damage in W and W-based alloys from 2 MeV self-ion near-bulk implantations

Abstract: The displacement damage induced in W and W-5 wt.% Re and W-5 wt.% Ta alloys by 2 MeV W + irradiation to doses 3.3×10 17-2.5×10 19 W + /m 2 at temperatures ranging from 300 to 750°C has been characterized by transmission electron microscopy. An automated sizing and counting approach based on Image J (a Java-based image processing program developed at the National Institutes of Health) [1] has been performed for all near-bulk irradiation data. In all cases the damage comprised dislocation loops, mostly of inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
94
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(108 citation statements)
references
References 57 publications
12
94
1
1
Order By: Relevance
“…Therefore, the defects in thin and thick samples can be expected to be different. However, for fast heavy ion irradiation, no difference was observed in a recent study in W [48], likely because the defect size is generally small in heavy ion irradiation. Our irradiation was carried out using rapid heavy ion irradiation conditions (around 10 min for 1 dpa).…”
Section: Effect Of Structure On the Precipitate Stabilitymentioning
confidence: 79%
“…Therefore, the defects in thin and thick samples can be expected to be different. However, for fast heavy ion irradiation, no difference was observed in a recent study in W [48], likely because the defect size is generally small in heavy ion irradiation. Our irradiation was carried out using rapid heavy ion irradiation conditions (around 10 min for 1 dpa).…”
Section: Effect Of Structure On the Precipitate Stabilitymentioning
confidence: 79%
“…Ciupi nski et al [26] and Yi et al [27] have used self-ion irradiation to study trends with dose (0.01e30 dpa) and irradiation temperature (300e1023 K) for <001>-grains 1 [28] of W and W-alloys, utilising cross-sectional and planar specimen geometries respectively. Both sets of authors confirmed that in Stage II, loops with b ¼ ½ <111> (~75%) and b ¼ <100> coexist, and were mostly 6 nm in diameter and interstitial in nature [22].…”
Section: Introductionmentioning
confidence: 99%
“…Interstitial-type dislocation loops form at those low irradiation temperatures in W-Ta alloys. The loop size is smaller and the loop number density is higher than in tungsten under equivalent irradiation conditions [19]. The low-temperature irradiation-hardening due to dislocation loops saturates at a damage level of 13 dpa at 300°C [20].…”
Section: Introductionmentioning
confidence: 90%
“…The low-temperature irradiation-hardening due to dislocation loops saturates at a damage level of 13 dpa at 300°C [20]. Ta is predicted to have a repulsive interaction with self-interstitial atom (SIA) defects such as \111[ crowdion [21] and dumbbell [22] configurations, and potentially restrict the mobility of SIAs and interstitial loops in W [19].…”
Section: Introductionmentioning
confidence: 99%